Authentic Diversity : How to change the workplace for good - Silverthorn, Michelle (Boca Raton Taylor and Francis Group, 2020)
"America is about to become a minority-majority nation. And yet, companies across the country do not reflect the transforming demographics of our nation, particularly with leadership. For decades, leaders have heard variations on the same theme on how to increase workplace diversity. It's time to stop following failing trends. It's time to lead change. In Make Diversity Matter, culture change expert and renowned speaker, Michelle Silverthorn, explains how to transform diversity and inclusion from mere lip service into the very heart of leadership. Following the journey of a young Black woman in the workplace, leaders learn the old rules of diversity that keep failing her and millions like her again and again, and the new rules they must put in place to make equity and inclusion a reality for everyone. A millennial, immigrant, and Black woman in America, Michelle Silverthorn will transform your understanding of diversity and inclusion in the workplace and equip you with the skills to successfully recruit, retain, and lead a diverse workforce. Change the rules, change the world. That's how great leaders make diversity matter for good"--
Keywords: General Management